Study of bacteria causing urinary tract infection and extended spectrum B-lactamases producing escherichia coli detected from patient visiting Dhulikhel hospital, Kavre. - Pandey, Santos (2011)
ABSTRACT: This study was carried out to determine the incidence of urinary tract infection (UTI) in patient visiting hospital. The samples were processed for macroscopic examination to observe leukocyte esterase and Nitrite by dipstick method, microscopic examination to observe pus cells, culture of urine sample on Blood agar and MacConkey agar to identify the potential pathogen. Colony count was evaluated and organisms were identified by Biochemical test. The identified bacteria were tested in vitro with standard antibiotic disc to determine their antibiotic sensitivity pattern and extended spectrum β-lactamases (ESBLs) producing E.coli were detected by combined discs method. Out of 329 samples, 80(23.30%) samples grew the bacterial pathogens that are responsible to cause urinary tract infection. Among them Escherichia coli 64(80%) was the predominant bacterial pathogen. Altogether 45(56.68%) multidrug resistant (MDR) strains were isolated. Multiple antibiotics resistance index (MARI) of antibiotics was found highest in antibiotics Ampicillin in Gram negative and Norfloxacin in Gram positive urine isolates. A total 13/64(20.31%) E. coli isolated were found to be ESBLs producers. The data obtained in this study highlight the problems of bacterial prevalence and resistance among uropathogenic bacteria. Keywords: UTI, MARI, ESBLs, uropathogens.